The Effect of Sample Weigh, Incubation Duration And Isolation Methods on The Quality of Phalaeonopsis amabilis root DNA - Handayani, Etty; Rineksane, Innaka Ageng; Isnawan, Bambang Heri; Setiawan, Haris Anggita; Manto, Agus (Tropical Plantation Journal, 2025)
Orchid Ph. amabilis is one of the plants designated as "Indonesian National Flower" and designated as "Puspa Pesona Indonesia". Orchid Ph. amabilis has a diversity that is not widely known, so that it is necessary to identify it molecularly. DNA isolation is the first step in molecular testing. This study aims to determine the sample weight, incubation time and the appropriate isolation method for DNA isolation from samples of Ph.amabilis orchid roots. In this study, the DNA isolation stage used two experimental methods, namely the CTAB method (Murray and Thompson) and the mini kit. The research method used was a single factor experiment with a combination of sample weight and incubation time consisting of 6 treatments with 3 replications, so 18 experimental units were obtained. The experimental treatment used was from the roots of the orchid Ph. amabilis which has a sample weight of 0.25 g, 0.5 g, and 0.75 g and each sample weight treatment was incubated for 30 minutes and 60 minutes. In addition, DNA isolation using the kit method had a sample weight of 0.25 g, 0.5 g and 0.75 g and an incubation period of 10 minutes. The results showed that the DNA isolation of Ph. amabilis with a sample weight of 0.75g, incubation time of 30 minutes using the CTAB method showed the best treatment in producing DNA with a concentration of 384 ng/µl and a purity of 1.9. This study is expected to provide information on sample weight, incubation time and the appropriate method for DNA isolation of Ph. amabilis orchid roots.